STUDENTS’ THINKING PROCESS IN CREATING SCHEMATIC REPRESENTATION - rahmad bustanul anwar; dwi rahmawati (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
The aim of this study is to describe students’ thinking process in creating schematic representation. A describtive qualitative research is used in this paper along with case study approach. The examined case is students’ thinking process in creating schematic representation in solving word problem. The subjects are Junior High School students at grade VIII. Data collection were done by think aloud technique and interview. The result show that students’ thinking process in creating schematic representation is retrieved from processing theory started by taking the problem into account. Students read the problem based on its intonation with stress in each sentence. Then, students create a scheme and link all information they understand about. This scheme later is drawn into triangle form. By creating the scheme, students are able to comprehend the questions and problems proper. Students connect problems faced by theirself with the concept of Phytagoras stored in long-term memory. The students' understanding of the Phytagoras Theorem concept is well preserved so that students can solve the problem appropriately.